2021
DOI: 10.1093/mtomcs/mfab057
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics reveals perturbations in the liver lipid profile of iron-overloaded mice

Abstract: Iron overload is an important contributor to disease. The liver, the major site of iron storage in the body, is a key organ impacted by iron overload. While several studies have reported perturbations in liver lipids in iron overload, it is not clear, on a global scale, how individual liver lipid ions are altered. Here, we used lipidomics to study the changes in hepatic lipid ions in iron-overloaded mice. Iron overload was induced by daily intraperitoneal injections of 100mg/kg body weight iron dextran for one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…Our data also expand on prior findings showing liver increases in the levels of taurine and methionine, suggestive that sulfur metabolism dysregulation follows organ-specific trends, which could be at least in part explained by microbial dysbiosis. Indeed, the deconjugation of taurine-conjugated bile acids is catalyzed by enzymes expressed by bacteria in the gut microbiome, whereby alterations of bile acid metabolism has been mechanistically implicated in inflammatory complications, such as macrophage activation, in the context of cholestasis, 51 trauma-induced microbiome alterations following decreased enteric perfusion, 52 bacterial infiltration in precancerous intraductal papillary mucinous neoplasms, 53 iron overload, 54 and nonalcoholic fatty liver disease. 55 Similar considerations can be made for several short-and odd-chain (carnitine-conjugated) fatty acids, increasing in the colon and stool following irradiation, especially when preceded by intravenous iron infusion.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our data also expand on prior findings showing liver increases in the levels of taurine and methionine, suggestive that sulfur metabolism dysregulation follows organ-specific trends, which could be at least in part explained by microbial dysbiosis. Indeed, the deconjugation of taurine-conjugated bile acids is catalyzed by enzymes expressed by bacteria in the gut microbiome, whereby alterations of bile acid metabolism has been mechanistically implicated in inflammatory complications, such as macrophage activation, in the context of cholestasis, 51 trauma-induced microbiome alterations following decreased enteric perfusion, 52 bacterial infiltration in precancerous intraductal papillary mucinous neoplasms, 53 iron overload, 54 and nonalcoholic fatty liver disease. 55 Similar considerations can be made for several short-and odd-chain (carnitine-conjugated) fatty acids, increasing in the colon and stool following irradiation, especially when preceded by intravenous iron infusion.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Kim et al have reported that high dietary iron intake is related to the incidence of diabetic peripheral neuropathy ( 28 ). The potential pathways may be iron overload that induces oxidative stress and triggers insulin resistance ( 29 , 30 ). Some recent studies found that iron released from ferritin is regulated by a process known as ferritinophagy, where the nuclear receptor coactivator 4 (NCOA4) directly binds the ferritin light chain and transfers the complex to the autolysosome for degradation ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Iron (Fe, from Latin: ferrum) caused experimental liver injury in animals [ 6 , 58 , 59 , 60 , 61 , 62 ]. This condition has to be differentiated from hereditary hemochromatosis, a human disease based on a genetic abnormality causing increased Fe levels preferentially in the liver [ 8 , 62 ].…”
Section: Ironmentioning
confidence: 99%
“…This condition has to be differentiated from hereditary hemochromatosis, a human disease based on a genetic abnormality causing increased Fe levels preferentially in the liver [ 8 , 62 ]. Mechanistic steps leading to experimental liver injury by Fe administrated in excess suggested a key role of hepatocellular oxidative stress generating ROS as responsible intermediate for apoptosis, lipid peroxidation, and reduced superoxide dismutase activity [ 58 , 59 ]. Studies on iron metabolism using the zebrafish model failed to contribute new aspects to the mechanistic steps [ 56 ].…”
Section: Ironmentioning
confidence: 99%